Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Vásquez Forero, Cristina Elizabeth (2019)
This analysis is about the company UNIQLO which is part of the Japanese group Fast Retailing. The study will examine the administrative and strategic aspects of this business at a global level, since it is already positioned in several countries. However it will mainly evaluate the different factors that are inherent to UNIQLO’s entrance into the Peruvian market. These factors would translate into its positioning and later success at a local level. It is important to add that the analysis carried out has highlighted the importance of different decisions that companies must make if they want to reach a place in the mind of the consumer, going from process management and current in the industry, the improvements in them, the implementations that will be developed when referring not only to the aspect as new equipment and systems, but also to the relations that must be established with the associated companies, obtaining advantages for all the parties with the will to obtain and always offer a good final product